Development Of Supply Chain Management Framework For Building Information Modelling Implementation In Public Sector Construction Projects - Ahmad, Nur Hidayah (2022)
Disputes have kept Building Information Modelling (BIM) from reaching its full potential. Consequently, this study attempts to reduce BIM implementation disputes in Malaysian public construction projects. Experts were involved in two phases of the mixed methods study. Phase 1 was a preliminary interview with six experts (to determine the need for reducing disputes among supply chain actors for BIM implementation). Meanwhile, Phase 2 began with a quantitative approach using the Fuzzy Delphi Method (FDM) on 14 experts to determine the main contributors that influence disputes (Objective Number 1). This was followed by qualitative approaches, namely self-grouping to identify the pathogens and pathogen sub-categories of disputes (Objective Number 2) and two sessions of Focus Group Discussion (FGD) involving six experts towards finally developing a validated SCM framework for BIM implementation (Objective Number 3). As a result of the quantitative approach, three main contributors that influence disputes were determined. The qualitative approach identified: (i) two pathogens as people issues, (ii) only one pathogen and two sub-pathogens as process problems, and (iii) product uncertainty is limited to one pathogen and one pathogen sub-category. Additionally, 15 appropriate SCM tools for dispute reduction were identified. In this vein, the study contributed theoretical, systematic, and practical BIM knowledge to current literature by demonstrating a solid understanding of SCM tool incorporation into BIM implementation for supply chain actors in Malaysian public projects